Associations Between Carotid Plaque Characteristics and Perioperative Cerebral Blood Flow Determined by Arterial Spin Labeling Imaging in Patients With Moderate-to-Severe Stenosis Undergoing Carotid Endarterectomy - Liu, Ying; Huo, Ran; Xu, Huimin; Zhou, Guangjin; Wang, Tao; Yuan, Huishu; Zhao, Xihai (Frontiers in Neurology, 2022)
Purpose To examine the associations between carotid plaque characteristics and perioperative cerebral blood flow (CBF) by arterial spin labeling (ASL) imaging. Materials and Methods Patients with unilateral moderate-to-severe carotid stenosis referred for carotid endarterectomy (CEA) were recruited and underwent carotid vessel wall and brain ASL magnetic resonance imaging. The following imaging features were measured: relative CBF (rCBF = CBFindex−hemisphere/CBFcontralateral−hemisphere) in the middle cerebral artery territory; plaque burden and the presence of lipid-rich necrotic core; intraplaque hemorrhage (IPH); calcification; ulcer and fibrous-cap rupture; and the volume and maximum plaque components' area percentages. The associations between plaque characteristics and perioperative CBF were analyzed. Results Sixty-one patients (mean age, 66.6 ± 7.8 years; 55 males) were included. Univariate linear regression showed that rCBFpre−CEA was associated with stenosis [β, −0.462; 95% confidence interval (CI), from −0.797 to −0.126; p = 0.008], calcification (β, 0.103; 95% CI, 0.005–0.201; p = 0.040), maximum IPH area percentage (β, −0.127; 95% CI, from −0.223 to −0.030; p = 0.012), and ulcer (β, 0.069; 95% CI, 0.025–0.113; p = 0.005); rCBFpost−CEA was associated with the IPH volume (β, −0.060; 95% CI, from −0.107 to −0.014; p = 0.013). After adjusting for the confounding factors, the associations of calcification with rCBFpre−CEA (β, 0.099; 95% CI, from 0.004 to −0.194; p = 0.042) and IPH volume with rCBFpost−CEA (β, −0.060; 95% CI, from −0.109 to −0.011; p = 0.020) remained statistically significant, while those of rCBFpre−CEA with maximum IPH area percentage (β, −0.089; 95% CI, from −0.188 to 0.011; p = 0.080) and ulcer (β, 0.050; 95% CI, from −0.012 to 0.112; p = 0.100) did not remain statistically significant. Conclusion The compositional characteristics of carotid atherosclerotic plaques, particularly IPH, were associated with perioperative CBF in patients with unilateral moderate-to-severe carotid stenosis undergoing CEA. Our findings indicated that the patients with larger carotid IPH could expect smaller improvement in CBF following CEA.